Poetry Reviews - Allan, Helen (LiNQ (Literature in North Queensland), 2016)
Silvana Gardner. When Sunday Comes, Brisbane: University of Queensland Press, 1982. Cloth 12.95, Paper 6.95. 46 pp. This recent publication, a first collection, is full of promise. It may prove a hard act to follow. If it doesn’t, we have a new poet of importance among us. First books are often autobiographical, either overtly or covertly. When Sunday Comes is in the former category, developing material won from the mine of personal experience. For Silvana Gardner is exploring a rich vein of childhood-toadolescence impressions deposited in the days when she was a child migrant to Australia. These impressions have obviously been of profound significance to her, and it happens fortuitously that the times in which we live lend them a certain significance for us.